1990
DOI: 10.1007/bf00120120
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal analysis and phylogenetic relationships in the Drosophila nasuta subgroup I. Phylogenetic relationships within the Drosophila sulfurigaster species complex

Abstract: Phylogenetic relationships within the Drosophila sulfurigaster species-complex, which belongs to the D. nasuta subgroup, were investigated on the basis of chromosomal constitution and morphology. D. pulaua is thought to be the most ancestral species, from which D. s. sulfurigaster and D. s. bilimbata derived in one branch and D. s. albostrigata and D. s. neonasuta in another branch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The nasuta subgroup species exhibit some features that make them evolutionarily interesting, such as various levels of reproductive isolation, extensive polymorphism of metaphase and polytene chromosomes, and extreme morphological similarity between females but strikingly different silver marking patterns in the male frons of different taxa (Nirmala and Krishnamurthy, 1972;Wilson et al, 1969;Kitagawa et al, 1982;Kitagawa, 1991). Despite extensive studies of morphometry (Wilson et al, 1969;Kitagawa et al, 1982;Kitagawa, 1991), reproductive isolation (Wilson et al, 1969;Kitagawa et al, 1982;Shao et al, 1997), chromosomes (Wilson et al, 1969;Kitagawa et al, 1982;Wakahama et al, 1983;Suzuki et al, 1990), proteins (Ramesh and Kalisch, 1989), and DNA (Chang et al, 1989;Tamura, 1992; our unpublished data of ribosomal internal transcribed spacer, ITS), the phylogenetic relationship among taxa in the subgroup is unclear. Even the taxonomy of the subgroup has changed several times.…”
Section: Introductionmentioning
confidence: 95%
“…The nasuta subgroup species exhibit some features that make them evolutionarily interesting, such as various levels of reproductive isolation, extensive polymorphism of metaphase and polytene chromosomes, and extreme morphological similarity between females but strikingly different silver marking patterns in the male frons of different taxa (Nirmala and Krishnamurthy, 1972;Wilson et al, 1969;Kitagawa et al, 1982;Kitagawa, 1991). Despite extensive studies of morphometry (Wilson et al, 1969;Kitagawa et al, 1982;Kitagawa, 1991), reproductive isolation (Wilson et al, 1969;Kitagawa et al, 1982;Shao et al, 1997), chromosomes (Wilson et al, 1969;Kitagawa et al, 1982;Wakahama et al, 1983;Suzuki et al, 1990), proteins (Ramesh and Kalisch, 1989), and DNA (Chang et al, 1989;Tamura, 1992; our unpublished data of ribosomal internal transcribed spacer, ITS), the phylogenetic relationship among taxa in the subgroup is unclear. Even the taxonomy of the subgroup has changed several times.…”
Section: Introductionmentioning
confidence: 95%
“…This implies that the distribution expansion of D. albomicans is likely attributed to the intraspecific variation including such strains that have a high cold tolerance and a strong acclimation response. It is noteworthy that D. pallidifrons, which is the most ancestral species in the D. nasuta subgroup (Wakahama et al, 1983;Suzuki et al, 1990), showed a relatively high cold tolerance after the cold acclimation (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…It's behavior conformed to that of D. sulfurigaster albostrigata (Spieth 1969, Waddell 1990, which is practically inseparable from that of D. s. neonasuta (Waddell 1990). Like Suzuki and Kitagawa (1990), we view neonasuta as a sub-population of albostrigata, and hence also a synonym. Further, rather than pollinosity across the whole frons, it had wide stripes of pollinosity on the frons along the orbits, exactly the morphology expected of D. s. albostrigata.…”
Section: Incongruent Phenotypes Among Extant Stocksmentioning
confidence: 98%